Lao Development Report 2014 : Expanding Productive Empoloyment for Broad-Based Growth - World Bank Group (Washington, DC, 2015)
Recent media reports of a perceived skills problem in Lao PDR have spurred an intense focus on skills development initiatives. Alarming media coverage of rising wages and complaints among firms of a shortage of skilled workers has raised concerns over whether Lao workers are equipped with the skills sought by firms. The Government and other partners have responded by channeling more resources to skills development, for example with investments in vocational training facilities to train more workers. This report argues that the workforce problems which Lao PDR faces do not only stem from problems in the education sector. Looking only to skills development as a solution would not address the fundamental problems constraining economic growth, employment creation, and poverty reduction. Creating an environment conducive for farm and non-farm businesses to make investments and grow remains an essential first step for skills development. As World Bank (2004) states, Training does not create jobs. Skills are a derived demand and that demand depends on policies for growth and employment creation.